Innovation for sustainability: exploring purpose-driven strategy and responsible innovation in small and medium-sized enterprises in Malaysia - Loo, Mun Chee (2023)
Malaysia’s economy growth is expected to be constrained by slowing traditional growth drivers, stretched fiscal position, and ageing population. One recommendation suggested by World Bank and adopted by the Government of Malaysia is for the nation to accelerate innovation to improve productivity. This is particularly important for the Small and Medium-sized Enterprises (“SMEs”) due to their significant contribution to the national economy, but SMEs are lagged in innovation capabilities. Concurrently the Government of Malaysia rolled out multiple national policies and initiatives to move the nation towards achieving the United Nations Sustainability Development Goals. These external factors are driving the need of innovation and sustainability and continue to pressure local firms to change their business model and practices. This research study aims to (i) explore how are SMEs developing their innovation and sustainability strategy, and (ii) develop a framework that can be a guide for local SMEs and start-ups to align innovation with sustainability. Through a review on extant literature, a framework is identified to analyse purpose-driven strategy and responsible innovation which consists of four dimensions – anticipation, inclusive deliberation, reflexivity, and responsiveness. The framework identified can help meeting the objectives of the study. By using these concepts, this study employs case study research to gain insight into the practices of successful local innovative SMEs which involve substantial sustainability efforts in their businesses. The final proposed framework from this research suggests that a firm should determine its company purpose to reconnect with the society and its company purpose must be integrated in the corporate strategy. This purpose-driven strategy shapes the direction for its innovation, which shall be guided by the four dimensions in the responsible innovation framework. Each dimension should be aligned to the company purpose through its activities. Firms must be cognisant that knowledge management and interactive learning is key in each dimension. This research study also discusses findings from the case studies based on this conceptual framework.